(untitled) (Annals of Medical Research, 2023)
Aim: In women, breast reduction surgery is performed due to macromastia, i.e., excessive breast size, regardless of age, and is the most effective method for eliminating problems such as dermatitis and malodor under breasts, as well as pain in the musculoskeletal system. To contribute to the establishment of standards that will ensure maximum patient comfort and minimum complications in the follow-up of breast reduction surgery, an operation frequently performed by plastic surgeons, by comparing the data of women who underwent breast reduction surgery without drains with those reported in the literature. Materials and Methods: Demographic and surgical record of 31 women who underwent bilateral breast reduction surgery performed by the same surgeon without the use of drains were evaluated retrospectively following the approval of the local ethics committee. Results: Breast reduction surgery was performed with the superomedial pedicle technique in 22 of the patients and the free nipple graft technique in nine. Early complications were seen in three (1.82%) of the total of 62 breasts that were operated on. Conclusion: The use of no drains in breast reduction surgery did not increase postoperative complications, and it also provided a more comfortable follow-up process for both the patient and the surgeon.